Role of Microbiota in Atopic Dermatitis and Bronchial Asthma - Triangular Cross-Talk among Skin, Airway and Gut - Kato, Yukihiko; Matsumura, Yasuhiro (Archives of Clinical and Biomedical Research, 2020)
The development of allergy is partly dependent on changes in individual’s microbiota which were interacted with the environment. Microbiota can be modulated by early-life microbial exposures, diet, antibiotics. Lower microbial diversity is pivotal factor in developing diseases. Certain types of microorganisms are involved in a disease activity. Early life exposure to non-pathogenic Proteobacteria has a protective effects in developing allergies. Later, bacterias, involving Staphylococcus aureus (S.aureus) in the skin or pathogenic Proteobacteria in the airway, affects patients with atopic dermatitis (AD) and bronchial asthma (BA) respectively. Similarly Acinetobacteria in early exposure protectively effect BA. The pathogenic role of Proteobacteria phylum might differ between bronchial and skin inflammation. The microbiota at local sites is also involved in the development and activity of diseases in remote organs via‘triangular cross talk’. Cross talk among skin, air way, and gut is not surprising, because they are the superficial organs. Lactobacilus in the Firmicutis phylum always protectively work for allergic diseases of skin and bronchus. Therefore probiotics, which mature the gut barrier and prime the immune function, are currently being used to prevent and treat AD and BA. The accumulated data, however, have failed to substantiate fully the effects of probiotics against allergic disorders.